Psychological Well-Being Among The New Primary School Teachers In Ouargla - Algeria (El-Wahat Journal for Research and Studies, 2025)
The study aimed to identify the level of psychological well-being among a sample of new primary school teachers in Ouargla province. It also sought to determine the relationship between the teacher's gender and specialization and their level of psychological well-being. To achieve the study objectives, a descriptive exploratory approach was adopted. The study relied on the Psychological Well-Being Index (PWI) by Cummins (translated by Tiliouine, 2009) and the Positive and Negative Affect Schedule (PANAS) by Watson, Clark, and Tellegen (1988), translated by Mesoudi (2016). The two scales were applied to a sample of 195 male and female teachers. The statistical analysis showed a high level of psychological well-being among the teachers, no differences between genders in psychological well-being, and no differences in PWB between Arabic, French, and English teachers.Keywords: Psychological well-being, Personal well-being Index, Positive and negative affect, Primary school teacher